Peran Komite Sekolah dalam Peningkatan Pelayanan Mutu Pendidikan di SDN Cibalongsari III - Siti Zahra Pajria; Undang Ruslan Wahyudin (Journal on Education, 2023)
This research aims to describe and analyze the role of the school committee in improving the quality of education services at SDN Cibalongsari III, Karawang Regency. This research was conducted using a qualitative approach with a case study design. Data was collected using field observation techniques and interviews with the head of the school committee of SDN Cibalongsari III informants. Not only that, the author adds a literature study that explores relevant data and information using various media, including a collection of written and unwritten sources. Based on the results of the study, it can be seen that the role of the school committee in improving the quality of education services at SD Negeri Cibalongsari III, Klari District, Karawang Regency is almost optimal in several roles including the role of the committee as a giver of consideration, and the role of the committee as a mediator. However, to improve the quality of education services at SDN Cibalongsari III, the school committee as an independent organization really needs support and cooperation with various parties as well as increasing the professionalism and competence of school committee administrators.